Decreased chromate uptake in Pseudomonas fluorescens carrying a chromate resistance plasmid. - Ohtake, H (1987)
CrO4(2-) resistance in Pseudomonas fluorescens LB300(pLHB1) was related to reduced uptake of CrO4(2-) relative to the plasmidless strain LB303. 51CrO4(2-) was transported mainly via the SO4(2-) active transport system; thus, cells grown with 0.15 mM cysteine, a repressor of the SO4(2-) transport system, were much more resistant to CrO4(2-) than those grown with 0.15 mM djenkolic acid, which derepressed the 35SrO4(2-) uptake system. Kinetics of 51CrO4(2-) uptake by P. fluorescens with and without the plasmid showed that the Vmax for 51CrO4(2-) uptake with the resistant strain was 2.2 times less than the Vmax for the sensitive strain, whereas the Km remained constant.